CTLA4, PD-1, PD-L1, PD-L2, TIM-3, TIGIT, and LAG3 DNA Methylation Is Associated With BAP1-Aberrancy, Transcriptional Activity, and Overall Survival in Uveal Melanoma. Issue 7 (22nd September 2022) - de Vos, Luka; Carrillo Cano, Tzaitel Maria; Zarbl, Romina; Klümper, Niklas; Ralser, Damian Johannes; Franzen, Alina; Herr, Emmanuelle; Gabrielpillai, Jennis; Vogt, Timo Jakob; Dietrich, Jörn; Strieth, Sebastian; Landsberg, Jennifer; et al.
Abstract : Uveal melanoma (UM) is an aggressive disease with poor response to oncological treatment, including immunotherapy. Loss of the epigenetic modifier BRCA1-associated protein 1 (BAP1) function drives UM oncogenesis and is associated with an immune-suppressive tumor microenvironment, poor prognosis, and a distinct DNA methylation and gene expression profile. Our study aimed to analyze comprehensively the DNA methylation status of the immune checkpoint genes PD-1, PD-L1, PD-L2, CTLA4, TIM-3 ( HAVCR2 ), TIGIT, and LAG3 and its association with mRNA expression, BAP1 -aberrancy, and patients' survival. We analyzed the DNA methylation landscape of immune checkpoint genes at single CpG resolution in N=80 UM samples provided by The Cancer Genome Atlas. We analyzed CpG methylation levels of the immune checkpoints with regard to their transcriptional signatures and patient outcomes.Methylation of specific CpG sites within the immune checkpoint genes PD-1, PD-L1, PD-L2, CTLA4, TIM-3, TIGIT, and LAG3 correlated strongly with mRNA expression levels, indicating a strong regulation of gene expression through DNA methylation. Moreover, immune checkpoint gene methylation was strongly associated with BAP1 -mutation status and associated with overall survival in UM. Our data indicate an epigenetic regulation of immune checkpoints through DNA methylation in UM. Further, our data highlight the prognostic significance of DNA methylation of immune checkpoint genes in UM thereby providing a rationale for methylation testing as predictive biomarkers for immunotherapy response.